The combination of Puerariae Lobatae Radix and Chuanxiong Rhizoma enhanced the absorption and pharmacokinetics of puerarin by modulating the intestinal barrier and influenced gut microbiota - Runzhi Chen; Peng Wu; Zheng Cai; Lan Tang; Ling Ye; Chuqi Hou; Na Yang; Jie Zhao (Journal of Functional Foods, 2018)
Puerarin, the most important flavonoid in Puerariae Lobatae Radix (PLR), has high biological activity but poor oral absorption. This study investigated how to enhance the absorption and pharmacokinetics of puerarin through modulating the intestinal barrier. Analyses of intestinal absorption, pharmacokinetics demonstrated enhanced puerarin absorption with daidzin, daidzein and ligustrazine (the main active ingredient in vinegar and Chuanxiong Rhizoma (CXR)). In particular, PLR combined with CXR enhanced the absorption and pharmacokinetics of puerarin through elevating puerarin solubility, regulating P-glycoprotein efflux and reducing claudin-5 expression. The combination of PLR and CXR reduced the diversity of gut microbiota and the ratio of Firmicutes to Bacteroidetes. In conclusion, combining PLR with CXR enhanced the absorption and pharmacokinetics of puerarin by modulating the intestinal barrier and influenced gut microbiota. The gut microbiota is likely to be a potential target for the combination of PLR and CXR.